1994
DOI: 10.1143/jjap.33.117
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Barium Niobates:*A New Class of Potential Substrates for YBa2Cu3O7-δSuperconductor

Abstract: A class of complex perovskites REBa2NbO6 (where RE=Pr, Nd, Sm and Eu) have been sintered as single phase materials having a high sintered density and stability, for their use as substrates for YBa2Cu3O7-δ superconductors. The structure of these materials was studied by X-ray diffraction technique and all of them were found to be isostructural having a cubic perovskite structure. These newly developed materials do not react with YBa2Cu3O7-δ superconductors even after annealing 1:1 volume mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…The substrate plays an important role in the development of good quality superconducting ential thermal analysis of sintered specimens was carried out to examine whether these compounds undergo phase films with high critical current density. Many compounds such as SrTiO 3 , MgO, and LaAlO 3 are in use as substrates transitions in the temperatures 300-1373 K using the Sieko TG/DTA Instrument (Model SSC/5200H, Sieko Instrufor YBa 2 Cu 3 O 7Ϫͳ (YBCO) films (5)(6)(7)(8). Even MgO, the most widely used substrate for YBCO superconductors ments Inc., Japan).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate plays an important role in the development of good quality superconducting ential thermal analysis of sintered specimens was carried out to examine whether these compounds undergo phase films with high critical current density. Many compounds such as SrTiO 3 , MgO, and LaAlO 3 are in use as substrates transitions in the temperatures 300-1373 K using the Sieko TG/DTA Instrument (Model SSC/5200H, Sieko Instrufor YBa 2 Cu 3 O 7Ϫͳ (YBCO) films (5)(6)(7)(8). Even MgO, the most widely used substrate for YBCO superconductors ments Inc., Japan).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were found to melt at ȁ2120 K. Thus melted samples were quenched in air and their phase purity was examined by XRD technique. For the chemical reactivity studies, the composites of Ba 2 RE TaO 6 and YBCO (prepared from high purity Y 2 O 3 , BaCo 3 , and CuO by solid state reaction) were prepared in 20 vol%-80 vol% ratio, respectively, and pressed pellets of the composites were heat treated up to 1223 K for 20 h in air and annealed at 733 K for 30 h under flowing oxygen. The chemical reactivity was studied by powder XRD and electrical resistivity measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [16][17][18]29] reported that complex perovskite compounds with non-cubic symmetry at room temperature are transformed to cubic at high temperature. Recently, these compounds have been reported as cubic by Koshy et al [20,32], as tetragonal by Zurmuhlen et al [17], as monoclinic by Henmi et al [27] and as cubic by Brixner [33] except Ba(La 1/2 Nb 1/2 )O 3 which is tetragonally distorted. In our XRD patterns an additional peak at 2θ ≈ 35 • is observed in all the compounds with t < 0.985 whereas it is completely absent in the materials with t > 0.985 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They obtained ε r in the range 30-45 and found that niobates and tantalates of Ba have positive τ f while those of Sr and Ca have negative τ f . Recently, several authors [16][17][18][19][20] reported the microwave dielectric properties of a few of theA(B 1/2 B 1/2 )O 3 type ceramics by direct microwave or spectroscopic methods. It was reported that the ε r value of Ba (Nd 1/2 Nb 1/2 )O 3 , Ba(Sm 1/2 Nb 1/2 )O 3 , Ba(Eu 1/2 Nb 1/2 )O 3 , and Ba(Pr 1/2 Nb 1/2 )O 3 as 12, 9, 11, and 15, respectively in the microwave frequency region [20] which were different from the report of Ikawa and Takemoto [21], and Zurmuhlen et al [17].…”
Section: Complex Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation